Progeria: An Accelerated Ageing Process - MEHTA A.K.; BABAR R.S.; PATIL K.S.; DUBAL A.P.; GUJAR P.P. (International Journal of Pharma and Bio Sciences, 2010)
Ageing is not a programmed process, in the sense that no genes are known to have evolved specifically to cause damage and ageing. An emerging consensus is that ageing is a consequence of macromolecular damage by reactive oxygen species, which oxidize lipids, proteins and, in particular, DNA, with damage to the latter leading to mutations and chromosomal abnormalities. Some rare congenital diseases, Hutchinson–Gilford Progeria syndrome (HGPS), Werner’s syndrome (WS) and Cockayne syndrome (CS) have attracted much interest, primarily because of their resemblance to an accelerated ageing process. Thus the mechanisms by which it takes place and the lamins which play a key role in maintaining cell and tissue integrity during ageing is the main part of the study. Thus, finding HGPS to be the result of pathogenesis rather than the result of true ageing may be exactly what we require for increasing understanding of the ageing process.